(untitled) (Amsterdam, 2016)
Nutraceuticals, the fourth volume in the Nanotechnology in the Agri-Food Industry series, is an invaluable resource for anyone in the food industry who needs the most current information about scientific advances in this field. Nutraceuticals are gaining significant attention because of their apparent safety, as well as their nutritional and therapeutic uses.
Keywords: Thực phẩm chức năng,Functional foods